The Use of Blended Cooperative Learning Model in Introduction to Digital Systems Learning - R. Ati Sukmawati; Mitra Pramita; Harja Santanapurba; Bekti Utami (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2020)
The purpose of this study is to analyze student learning outcomes in the application of the blended cooperative learning model, and analyze students' perceptions about the application of the cooperative blended learning model. Quantitative and qualitative research methods were used together with 91 subjects as participants in Introduction to Digital Systems academic year 2018/2019. Data was collected by tests, questionnaires, observations and video recordings. The results showed that the student learning outcomes were in the sufficient category. Students showed a positive perception of the implementation of the blended cooperative learning model, but they still need more encouragement to be more independent in learning.